Features of commercialization of international information projects in the context of European integration - Mekhovych, S. A.; Poberezhnyi, R. O.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
The development of research and development consists in their commercialization. The scientific development of innovations in the context of European integration should be profitable. Therefore, in order for an innovative project to pay off and bring profit, it is necessary to commercialize it.
Keywords: technology transfer; commercialization; information activities; European integration